Epidemiology of antimicrobial resistant diarrheagenic Escherichia coli pathotypes from children, livestock and food in Dagoretti South, Nairobi Kenya - Okumu, Noah O.; Muloi, Dishon M.; Moodley, Arshnee; Ochieng, Linnet; Watson, J.; Kiarie, Alice; Ngeranwa, J.J.N.; Cumming, O.; Cook, Elizabeth A.J. (Elsevier, 2025)
Peri-urban environments, characterized by dense human populations, cohabiting livestock, and complex food systems, serve as hotspots for food contamination and infectious diseases. Children aged 6-24 months are particularly vulnerable as they often encounter contaminated food and water, increasing their risk of food-borne disease, with diarrhea being a common symptom. We investigated the prevalence of antimicrobial resistance (AMR) in pathogenic Escherichia coli from 6-24 months-old children, their food, and cohabiting livestock, in Dagoretti South subcounty in Nairobi, Kenya. Out of 540 stool, 296 livestock feces and 859 food samples collected from 585 randomly enrolled households, 16% harbored diarrheagenic E. coli (DEC) pathotypes. The predominant AMR phenotypes observed were trimethoprim-sulfamethoxazole, ampicillin, and tetracycline at 53%, 48% and 41%, respectively. Diarrheagenic E. coli from children showed significantly higher resistance to all antibiotics compared to those from livestock and food. Overall, 30% of the 274 DEC isolates from all three sources exhibited multidrug resistance. Network analysis of AMR co-occurrence revealed two clusters: 1) ampicillin, trimethoprim-sulfamethoxazole, tetracycline, amoxicillin/clavulanic acid, and chloramphenicol, and 2) nalidixic acid, ciprofloxacin, gentamicin, and ceftriaxone. Co-resistance backbone of ampicillin-trimethoprim/sulfamethoxazole-tetracycline was significantly higher among children isolates than other hosts (χ² = 29.858, df = 2, adjusted p < 0.05). Logistic regression analysis revealed that on-site disposal of animal manure and garbage, along with a recent history of diarrhea, were significantly associated with AMR carriage in children (p < 0.05). These findings emphasize the need for One Health interventions to curb emergence and spread of AMR in these close contact populations.